(untitled) (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: The purpose of this research is to evaluate the effectiveness of video media through the TikTok application in increasing teenagers’ knowledge about Clean and Healthy Living Behavior at the junior high school level. Methodology: This research method is quantitative, using a questionnaire as the main instrument for collecting data which is distributed to students. The collected data was then analyzed using descriptive and inferential statistical techniques to evaluate the relationship between the use of TikTok video media and teenagers’ knowledge about Clean and Healthy Living Behavior. Main Findings: The results of this research are that the use of video media through the TikTok application significantly increases teenagers’ knowledge about Clean and Healthy Living Behavior at the Junior High School level. These findings demonstrate the great potential of the use of social media platforms in increasing adolescent health awareness and emphasize the importance of further exploration of innovative health education approaches. Novelty/Originality of this study: The novelty of this research lies in exploring the effectiveness of using video media through the TikTok application in increasing teenagers’ knowledge about Clean and Healthy Living Behavior at the Junior High School level, which highlights the importance of adapting health education strategies to developing digital trends.